Repeatability of three-dimensional thorax and pelvis kinematics in the golf swing measured using a field-based motion capture system - Evans, K.; Horan, S. A.; Neal, R. J.; Barrett, R. S.; Mills, P. M. (Sports Biomechanics, 2012)
Field-based methods of evaluating three-dimensional (3D) swing kinematics offer coaches and researchers the opportunity to assess golfers in context-specific environments. The purpose of this study was to establish the inter-trial, between-tester, between-location, and between-day repeatability of thorax and pelvis kinematics during the downswing using an electromagnetic motion capture system. Two experienced testers measured swing kinematics in 20 golfers (handicap <= 14 strokes) on consecutive days in an indoor and outdoor location. Participants performed five swings with each of two clubs (five-iron and driver) at each test condition. Repeatability of 3D kinematic data was evaluated by computing the coefficient of multiple determination (CMD) and the systematic error (SE). With the exception of pelvis forward bend for between-day and between-tester conditions, CMDs exceeded 0.854 for all variables, indicating high levels of overall waveform repeatability across conditions. When repeatability was compared across conditions using MANOVA, the lowest CMDs and highest SEs were found for the between-tester and between-day conditions. The highest CMDs were for the inter-trial and between-location conditions. The absence of significant differences in CMDs between these two conditions supports this method of analysing pelvis and thorax kinematics in different environmental settings without unduly affecting repeatability.